Modern analysis of litigation related to bullying (bullying) by participants in the educational process in Ukraine - Sobol, Yevhen (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article considers and analyzes six lawsuits related to bullying (harassment) by participants in the educational process in Ukraine. It is noted that this analysis of court cases is carried out in order to further form specific proposals to improve the effectiveness of measures aimed at minimizing such a socially negative phenomenon as bullying. It is indicated that today court cases are characterized by the lack of a unified approach to resolving typical (ie those in which the composition of an administrative offense is the same or quite similar) cases. It is noted that this is due to the fact that this category of bullying, as well as legal responsibility for its commission is a fairly new phenomenon for modern jurisprudence, which directly determines the difficulty of making unified decisions. It is emphasized that the lack of a clear understanding of the essential component of the category «bullying» and its characteristics in practice complicates the process of identification of bullying not only during the trial, but also at the stage of drawing up reports on administrative offenses. It is concluded that in Ukraine it is necessary to take a comprehensive approach to the category of bullying not only theorists, scientists, but also judges, employees of the National Police and other officials, because the consequences of bullying, as case law shows, may be depressed, reluctance to visit educational institution, the need for psychological assistance, etc., which negatively affects the further socialization of the person who became a victim of bullying. Emphasis is placed on the fact that the study of issues related to the administrative and legal mechanism for preventing this negative phenomenon is a promising area of research.